APAKAH SIKAP MAMPU MEMODERASI HUBUNGAN ANTARA DUKUNGAN DAN KINERJA MANAJEMEN RISKO? - Moelyono, Yosia; Valerian, Vincent; Kountur, Ph.d, Ronny (Journal of Management and Business Review, 2019)
The purpose of this study is to know whether management attitudes can moderate the relationship between management support and risk management performance. Respondents from 112 companies were taken.  They were the top rank risk management personal in those companies.  Questionnaire was designed in collecting the data.  The validity and reliability of the questionnaire has been tested.  Multiple regression analysis techniques were used to test the null hypothesis that attitude is the moderating variable between management support and risk management performance.  The null hypothesis was accepted indicating that attitude toward risk management was not a moderating variable in the relationship between management support and risk management performance.  However further analysis with the use of path analysis found that management support instead was the mediating variable between attitudes and performance of risk management. Therefore, when top management has positive attitude toward risk management will increase the risk management performance of the organization.